In Silico Identification of Clinically Approved Medicines Against the main Protease of Sars-Cov-2 – A Causative Agent of Covid-19: Life Sciences-Zoology - Estari Mamidala; Rakesh Davella; Swapna Gurrapu; Pujala Shivakrishna (International Journal of Life Science and Pharma Research, 2022)
The COVID-19 pandemic triggered by SARS-CoV-2 is a worldwide health disaster. Main protease is an attractive drug target among coronaviruses, due to its vital role in processing the polyproteins that are translated from the viral RNA. There is presently no exact drug or treatment for this disease caused by SARS-CoV-2.Speeding up drug innovation is immediately required. In the present study, we report the potential inhibitory activity of some FDA approved drugs against SARS-CoV-2 main protease by molecular docking study to investigate their binding affinity in protease active sites. Total 47 FDA approved drugs were selected for molecular docking with main COVID-19 protease. The docking of selected drugs to the active site of protein was performed using AutoDock software. Docking was achieved to attain a population of potential conformations and alignments for the ligand at the binding site. Docking study revealed that great inhibitory efficacy of the one anti-H1N1 drug (Oseltamivir), one anti-TB drug (Rifampin), four anti-HIV drugs (Maraviroc, Etravirine, Indinavir, Rilpivirine) and seven anti- malarial drugs (Atovaquone, Quinidine, Halofantrine, Amodiaquine, Tetracylcine, Azithromycin, hydroxycholoroquine) was found since they could launch H2 bonds with different amino acid residues that caused an inhibition of SARS-CoV-2 protease activity with higher binding affinity ranging from (-10.67 to -8.3 kcal/mol). However, the in-silico abilities of the drug molecules tested in this study, further needs to be validated by carrying out in vitro and in vivo studies. Moreover, this study spreads the potential use of current drugs to be considered and used to comprise the fast expanding SARS-CoV-2 infection.